Elucidating the Surface Functionality of Biomimetic RGD Peptides Immobilized on Nano-P(3HB-co-4HB) for H9c2 Myoblast Cell Proliferation - Vigneswari, Sevakumaran; Chai, Jun Meng; Kamarudin, Khadijah Hilmun; Amirul, Al-Ashraf Abdullah; Focarete, Maria Letizia; Ramakrishna, Seeram (Frontiers in Bioengineering and Biotechnology, 2020)
Biomaterial scaffolds play crucial role to promote cell proliferation and foster the regeneration of new tissues. The progress in material science has paved the way for the generation of ingenious biomaterials. However, these biomaterials require further optimization to be effectively used in existing clinical treatments. It is crucial to develop biomaterials which mimics structure that can be actively involved in delivering signals to cells for the formation of the regenerated tissue. In this research we nanoengineered a functional scaffold to support the proliferation of myoblast cells. Poly(3-hydroxybutyrate-co-4-hydroxybutyrate) [P(3HB-co-4HB)] copolymer is chosen as scaffold material owing to its desirable mechanical and physical properties combined with good biocompatibility, thus eliciting appropriate host tissue responses. In this study P(3HB-co-4HB) copolymer was biosynthesized using Cupriavidus malaysiensis USMAA1020 transformant harbouring additional PHA synthase gene, and the viability of a novel P(3HB-co-4HB) electrospun nanofiber scaffold, surface functionalized with RGD peptides, was explored. In order to immobilize RGD peptides molecules onto the P(3HB-co-4HB) nanofibers surface, an aminolysis reaction was performed. The nanoengineered scaffolds were characterized using SEM, organic elemental analysis (CHN analysis), FTIR, surface wettability and their in vitro degradation behaviour was evaluated. The cell culture study using H9c2 myoblast cells was conducted to assess the in vitro cellular response of the engineered scaffold. Our results demonstrated that nano-P(3HB-co-4HB)-RGD scaffold possessed an average fiber diameter distribution between 200 nm and-300 nm, closely biomimicking, from a morphological point of view, the structural ECM components, thus acting as potential ECM analogues. This study indicates that the surface conjugation of biomimetic RGD peptide to the nano-P(3HB-co-4HB) fibers increased the surface wettability (15 ± 2o) and enhanced H9c2 myoblast cells attachment and proliferation. In summary, the study reveals that nano-P(3HB-co-4HB)-RGD scaffold can be considered a promising candidate to be further explored as cardiac construct for building cardiac construct.